Probing magnetic properties at the nanoscale: in-situ Hall measurements in a TEM - Darius Pohl; Yejin Lee; Dominik Kriegner; Sebastian Beckert; Sebastian Schneider; Bernd Rellinghaus; Andy Thomas (Scientific Reports, 2023)
Abstract We report on advanced in-situ magneto-transport measurements in a transmission electron microscope. The approach allows for concurrent magnetic imaging and high resolution structural and chemical characterization of the same sample. Proof-of-principle in-situ Hall measurements on presumably undemanding nickel thin films supported by micromagnetic simulations reveal that in samples with non-trivial structures and/or compositions, detailed knowledge of the latter is indispensable for a thorough understanding and reliable interpretation of the magneto-transport data. The proposed in-situ approach is thus expected to contribute to a better understanding of the Hall signatures in more complex magnetic textures.